Using Your Beam Efficiently: Reducing Electron Dose in the STEM via Flyback Compensation. (August 2022) - Mullarkey, Tiarnan; Peters, Jonathan J. P.; Downing, Clive; Jones, Lewys
Abstract: Abstract : In the scanning transmission electron microscope, fast-scanning and frame-averaging are two widely used approaches for reducing electron-beam damage and increasing image signal noise ratio which require no additional specialized hardware. Unfortunately, for scans with short pixel dwell-times (less than 5 μ s), line flyback time represents an increasingly wasteful overhead. Although beam exposure during flyback causes damage while yielding no useful information, scan coil hysteresis means that eliminating it entirely leads to unacceptably distorted images. In this work, we reduce this flyback to an absolute minimum by calibrating and correcting for this hysteresis in postprocessing. Substantial improvements in dose efficiency can be realized (up to 20%), while crystallographic and spatial fidelity is maintained for displacement/strain measurement.